Pengaruh Spiritualitas Kerja terhadap Keterlekatan Karyawan melalui Kepuasan Kerja pada UKM Kota Bogor - Nur Janah; Anggraini Sukmawati; Farit Mochamad Afendi (IPB University, 2017)
The Quality human resources are needed in global economic competition. Spirituality in work becomes a solution developed by companies, because it can be created a conducive environment for employees to work as good as possible. The purpose of this study is to analyze the influence of work spirituality on employee engagement through job satisfaction in Small and Medium Enterprises cluster of food and beverages in the city of Bogor. This research used Structural Equation Modeling PLS for data analysis. Samples are SMEs that have at least 5 employees and have been registered in the Department of Industry and Trade (Disperindag) and the Department of Cooperatives and SMEs Bogor City. So that 25 SMEs are eligible, consisting of 65 people consisting of employees and owners of SMEs. Sampling method using purposive sampling. The results showed that the spirituality of work has a positive effect directly on employee engagement and indirectly influence through job satisfaction on employee engagement to the organization. Meanwhile, job satisfaction has a direct positive effect on employees' engagement to the organization. Therefore, increased employee engagement to SMEs is suggested through several supporting activities such as: communicating and facilitating the need for spirituality in the workplace.